Situation and development trends of the food industry - Felkai Beáta Olga; Kuti Beatrix (WESSLING Nemzetközi Kutató és Oktató Központ Közhasznú Nonprofit Kft. Budapest, 2022)
The food industry in Hungary has come a long way from the 1800s to the present day and is still facing many challenges. It is a highly heterogeneous sector with a large number of employees, whose uniqueness and specificities have a significant impact on its present and potential. Its development potential lies in increasing added value, moving towards quality products, and positioning itself on domestic and export markets. The pace of development is determined by strategies, subsidies, the regulatory environment, R&D&I opportunities, consumer needs and related education, the availability and variability of raw materials, strict food safety requirements, etc. In this article, we present the past, present and development trends of the food industry based on the lecture 100+10 years of food science at the 240th anniversary of the Budapest University of Technology on 19 November 2021.
Keywords: Műszaki és technológiai tudományok; Egyéb műszaki tudományok és technológiák; Élelmiszer és italfélék